Amidst COVID-19 pandemic: the catastrophic sequelae of an inadvertent carotid artery insertion during central venous catheter placement – a case report. Issue 5 (3rd September 2021) - Tanveer Ud Din, Mian; Nasrullah, Adeel; Sarma, Deeksha; Ashraf, Obaid; Arshad, Hammad
ABSTRACT: Introduction : Central venous catheter (CVC) placement is one of the most commonly performed procedures in the intensive care unit for the institution of high-risk medications and nutrients. Despite the frequent use of ultrasound, inadvertent placement of CVC into the carotid artery is still possible. It carries significant morbidity due to the incidence of bleeding, arteriovenous fistula, and stroke. Methods : We present a case of accidental placement of CVC into the right carotid artery, which led to the right-sided temporoparietal stroke. Case Summary : A 71-year-old male was admitted to hospital with symptoms of cough, fatigue, and shortness of breath. He was diagnosed with coronavirus disease-19 and did require mechanical ventilation due to progressive hypoxic respiratory failure. The patient developed distributive shock and underwent CVC placement at the day of admission. On the 24th day of intubation, the patient was unable to move his left upper and lower extremities. Computed tomography (CT) head revealed showed a large temporoparietal stroke. CT Angiogram of head and neck revealed a misplaced CVC within the right common carotid artery . He was transferred to the Neuro ICU at our hospital where the patient underwent catheter removal and carotid artery sheath placement followed by dual antiplatelet therapy. Although the patient survived, he still required long-term facility placement due to the stroke. Conclusion : We reiterate that an experienced clinician must perform the CVC placement with ultrasound guidance and verify its placement with multiple confirmation techniques afterwards. Providers must manage unintentional carotid artery placement promptly to prevent long-term sequelae associated with it.